2015
DOI: 10.1186/1471-2288-15-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research and medical care: towards effective and complete integration

Abstract: BackgroundDespite their close relationship, clinical research and medical care have become separated by clear boundaries. The purpose of clinical research is to generate generalizable knowledge useful for future patients, whereas medical care aims to promote the well-being of individual patients. The evolution towards patient-centered medicine and patient-oriented research, and the gradual standardization of medicine are contributing to closer ties between clinical research and medical practice. But the integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 58 publications
0
39
0
3
Order By: Relevance
“…Health professionals’ perception of progressive divergence between clinical research and standard health care has been reported to have serious repercussions on the professional practice of CRNs (Bowers, ). Sacristán () found that despite their close relationship, clinical research and medical care have become separated by clear boundaries and their integration required researchers, clinicians, healthcare managers and patients to re‐evaluate the way they understand research, in relation to the potential benefits for present and future patients. CRNs membership in clinical research enterprise was reported as an ongoing struggle to establish the significance and validity of their service within standard care settings:
Once you establish that we (CRN and non‐research colleague) are not enemies here and some of the studies that we have got a drug which is very advantageous to this kind of disease…and you work together, it's good.
…”
Section: Challenges Of Crn Identitymentioning
confidence: 99%
“…Health professionals’ perception of progressive divergence between clinical research and standard health care has been reported to have serious repercussions on the professional practice of CRNs (Bowers, ). Sacristán () found that despite their close relationship, clinical research and medical care have become separated by clear boundaries and their integration required researchers, clinicians, healthcare managers and patients to re‐evaluate the way they understand research, in relation to the potential benefits for present and future patients. CRNs membership in clinical research enterprise was reported as an ongoing struggle to establish the significance and validity of their service within standard care settings:
Once you establish that we (CRN and non‐research colleague) are not enemies here and some of the studies that we have got a drug which is very advantageous to this kind of disease…and you work together, it's good.
…”
Section: Challenges Of Crn Identitymentioning
confidence: 99%
“…For PCM, it is necessary to treat individual patients according to their heterogeneous characteristics [18]. The development of PCM requires patient-oriented research, focused on the individualization of results, disaggregation of data, and analysis of differences in subgroups [19]. Patients generally have many attributes, thus, previous studies using conventional subgroup analyses are limited, as classifications were based on a single variable (e.g., male vs. female, elderly vs. young) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Publications on strategies to improve recruitment rates, to retain participants in clinical research, and to facilitate researcher‐clinician collaboration reported difficulties in combining clinical and research roles, where the main reasons were the lack of time, ethical concerns, and absence of leadership, particularly in the field of nursing . The discussed models of combining clinical and research activities in various health fields were collaboration, partnership, and integration . However, the process of routinisation of RCTs in clinical practice has not been discussed as a holistic process and as a separate model, including in the field of wound management.…”
Section: Introductionmentioning
confidence: 99%
“…33 The discussed models of combining clinical and research activities in various health fields were collaboration, partnership, and integration. [34][35][36][37] However, the process of routinisation of RCTs in clinical practice has not been discussed as a holistic process and as a separate model, including in the field of wound management. In this article, we have developed the Routinisation of Trials Framework, analysing practical suggestions offered by clinical and research nurses from the Australian wound clinics.…”
Section: Introductionmentioning
confidence: 99%